2008
DOI: 10.7589/0090-3558-44.3.707
|View full text |Cite
|
Sign up to set email alerts
|

Nephrolithiasis and Pyelonephritis in Two West Indian Manatees (Trichechus manatus spp.)

Abstract: Two West Indian manatees (Trichechus manatus spp.) were reported with severe emaciation. One animal was a Florida manatee from the Everglades; the other was an Antillean manatee from Cuba. On necropsy, both animals had nephrolithiasis, pyelonephritis, and moderate to severe renomegaly. Histopathology revealed multifocal to diffuse pyelonephritis, interstitial nephritis, and nephrocalcinosis. The stones were analyzed and consisted primarily of calcium carbonate. Serum chemistry values for the Florida animal rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Nephroliths in marine mammals can lead to ureteral and urethral obstruction, hydronephrosis, kidney atrophy, and loss of function (Dennison et al 2007, Keller et al 2008, Venn-Watson et al 2008, as was also evident in the present study's population of dolphins. As such, the MMP is striving to treat and prevent nephrolithiasis in dolphins.…”
Section: Clinical Significance Of Nephrolithiasis In Dolphinssupporting
confidence: 69%
See 1 more Smart Citation
“…Nephroliths in marine mammals can lead to ureteral and urethral obstruction, hydronephrosis, kidney atrophy, and loss of function (Dennison et al 2007, Keller et al 2008, Venn-Watson et al 2008, as was also evident in the present study's population of dolphins. As such, the MMP is striving to treat and prevent nephrolithiasis in dolphins.…”
Section: Clinical Significance Of Nephrolithiasis In Dolphinssupporting
confidence: 69%
“…Nephrolithiasis has been reported in few marine mammals, including a northern elephant seal, a harbor seal, a California sea lion, and 2 West Indian manatees (Stroud 1979, Dennison et al 2007, Keller et al 2008. We previously reported a case of end-stage renal disease associated with urate nephrolithiasis in an adult male bottlenose dolphin Tursiops truncatus (Venn-Watson et al 2008).…”
Section: Introductionmentioning
confidence: 94%
“…Reports of fibro-purulent bronchopneumonia and chronic kidney diseases in Antillean manatee are rare and poorly described. Keller et al (2008) described the multifocal to diffuse pyelonephritis, interstitial nephritis and nephrocalcinosis in West Indian manatees. On the other hand, Deninson et al (2007) showed urate nephrolithiasis in a northern elephant seal (Mirounga angustirostris) and a california sea lion (Zalophus californianus).…”
Section: Discussionmentioning
confidence: 99%
“…28 Although significant rescue and rehabilitation efforts are in place, few reports of renal pathology in Florida manatees exist in the veterinary literature, and renal compromise is an underexplored area in the medical rehabilitation of sirenians. 12,14,18,19 These animals frequently present dehydrated on arrival to critical care facili-ties, 7 may have sustained direct trauma to the kidneys via boat strikes (as the kidneys lie caudodorsally in the abdominal cavity, making them prone to fractures), and may experience ischemic events related to coagulation disorders. 3,18 Clinicians are limited to analysis of blood urea nitrogen (BUN), creatinine levels, and urinalysis (if a urine sample can be obtained) in order to evaluate renal function, which may not accurately reflect renal function.…”
Section: Introductionmentioning
confidence: 99%